2017
DOI: 10.18632/oncotarget.22165
|View full text |Cite
|
Sign up to set email alerts
|

Super enhancer associated RAI14 is a new potential biomarker in lung adenocarcinoma

Abstract: PurposeTyrosine kinase inhibitors (TKIs) are widely used to treat lung adenocarcinoma patients with EGFR mutations or ALK-fusions. However, patients with wild-type genes or TKIs-resistant mutations lack effective therapeutic targets. Extensive studies reveal that super enhancer (SE), a large cis-regulatory element, is associated with key oncogenes in a variety of cancers. By comparing the effect of SE on lung adenocarcinoma cell lines with normal cell line, this work attempts to find new biomarkers and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Tippens and colleagues (15) reported that enhancers and promoters harbored more similarities than expected. Promoters capable of bidirectional transcription are associated with enhancer activity (14), and the transcribed enhancer RNAs have been proposed to contribute to enhancer activity (24)(25)(26). The bidirectional transcription ability has been verified by luciferase activity and the chromatin state segmentation from ENCODE also predicted this promoter region with enhancer potential.…”
Section: Discussionmentioning
confidence: 94%
“…Tippens and colleagues (15) reported that enhancers and promoters harbored more similarities than expected. Promoters capable of bidirectional transcription are associated with enhancer activity (14), and the transcribed enhancer RNAs have been proposed to contribute to enhancer activity (24)(25)(26). The bidirectional transcription ability has been verified by luciferase activity and the chromatin state segmentation from ENCODE also predicted this promoter region with enhancer potential.…”
Section: Discussionmentioning
confidence: 94%
“… 12 14 SEs are reported to be enriched at oncogenes in cancer cells, which are generated and activated through chromosomal rearrangements, focal amplification, and upregulation of transcription factors. 11 , 14 , 15 As confirmed by multiple research works, the upregulation of SE is involved in the tumor pathogenesis. 16 Besides that, SEs in cancer cells are more susceptible to perturbation as compared with the typical enhancer, which leads to a more pronounced impairment of the expression of SEs-related genes.…”
Section: Introductionmentioning
confidence: 79%
“…RAI14 has been proved as an SE associated gene that is upregulated in lung adenocarcinoma and impacts the cell proliferation. 11 To the best of our understanding, no data are available to indicate the relationship between RAI14 and gastric cancer. In our study, we observed that the expression of RAI14 was upregulated in gastric cancer and the RAI14 expression level was correlated with the prognosis of gastric cancer patients, indicating that RAI14 might be involved in progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, oncogenic activity was showed for RAI14, also named as novel retinal pigment epithelial cell gene (NORPEG), found to be aberrantly up-regulated in lung adenocarcinoma [249], and gastric cancer [250]. Recently, high expression of RAI14 in gastric cancer tissues, compared to matched normal tissues, was related to unfavourable patients' prognosis [251].…”
Section: Retinoid-inducible Gene 1 (Rig1) Hypermethylationmentioning
confidence: 99%